EMPHYSEMATOUS PYELONEPHRITIS: A REVIEW OF SIX CASES - Ali, Sohrab Naushad; Ahmed, Niqad; Naushad, Aymon; Naushad, Mian (Journal of Ayub Medical College Abbottabad, 2014)
Background: Emphysematous pyelonephritis is a severe life threatening necrotising infection of the renal parenchyma. The infection most commonly occurs in the diabetic population, often associated with the organism E. coli. Emphysematous pyelonephritis differs from standard pyelonephritis by the bacterial liberation and accumulation of gas in the surrounding tissues. The condition is rarely encountered in clinical practice and since the first description by Kelly et al in 1898, approximately 200 cases have been reported in the literature. Methods: The case series examines our experience with six diagnosed cases of emphysematous pyelonephritis over a one year period. Results: All patients were female, the mean age of presentation being 53 years. Of the six patients, five were diabetics with hypertension, the one exception being a non-diabetic patient who had undergone renal exploration in the past. Computed tomography confirmed the diagnosis in all patients except one which was confirmed during renal exploration. Urine culture was positive for E. coli in two patients. Conclusion: Emphysematous pyelonephritis which used to be a rare disease is now being more readily diagnosed. The cases were diagnosed at a late stage making its conservative management not feasible Keywords: Emphysematous pyelonephritis, renal infections, nephrectomy, renal parenchyma